Sputum interleukin‐13 as a biomarker for the evaluation of asthma control. Issue 7 (3rd May 2016) - Tsilogianni, Z.; Hillas, G.; Bakakos, P.; Aggelakis, L.; Konstantellou, E.; Papaioannou, A. I.; Papaporfyriou, A.; Papiris, S.; Koulouris, N.; Loukides, S.; Kostikas, K.
Summary: Background: Asthma control refers to the extent to which the manifestations of asthma have been reduced or eradicated by treatment. Interleukin‐13 (IL‐13) has a central role in Th2 response and serves as a possible therapeutic target in uncontrolled asthma. Fraction of exhaled nitric oxide (FeNO) and sputum eosinophils have modest performance in the evaluation of asthma control. Objective: To assess the diagnostic performance of sputum IL‐13 for the evaluation of asthma control and furthermore to investigate the performance of sputum eosinophils and FeNO. Methods: One hundred and seventy patients with asthma were studied. All subjects underwent assessment of asthma control by asthma control test (ACT), lung function tests, FeNO measurement and sputum induction for cell count identification and IL‐13 measurement in supernatants. Results: IL‐13 (pg/mL) levels in sputum supernatant differed significantly among patients with well‐controlled asthma and those with not well‐controlled asthma [median IQR 78 (66–102) vs. 213 (180–265), P < 0.001]. Receiver operating characteristic (ROC) analysis showed that, for the whole study population, the diagnostic performance of IL‐13 was superior to both sputum eosinophils and FeNO levels [area under the curve (AUC) 0.92, 95% CI 0.87 to 0.95 vs. AUC 0.65, 95% CI 0.58 to 0.72 vs. AUC 0.65, 95% CI 0.55 to 0.72, respectively]. Conclusion: The diagnostic performance of sputum IL‐13 was superior to both sputum eosinophils and FeNO levels for the identification of well‐controlled asthma. Sputum IL‐13 levels could serve as a useful biomarker for asthma control assessment.